2021
DOI: 10.1021/acsomega.1c04139
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and Enhanced Antimicrobial Inhibition of Mesoporous ZnO–Ag2O/Ag, ZnO–CuO, and ZnO–SnO2 Composite Nanoparticles

Abstract: In this work, mesoporous (pore size below 4 nm) composite nanoparticles of ZnO–Ag2O/Ag, ZnO–CuO, and ZnO–SnO2 of size d ≤ 10 nm (dia.) have been synthesized through the in situ solvochemical reduction method using NaBH4. These composite nanoparticles exhibited excellent killing efficacy against Gram-positive/negative bacterial and fungal strains even at a very low dose of 0.010 μg/mL. Additionally, by applying the in silico docking approach, the nanoparticles and microorganism-specific targeted proteins and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…The surface morphology of KCl-CuO/SnO 2 was investigated by high-resolution TEM (HRTEM). As shown in Figure i, the interplanar spacings ( d ) were 2.32, 2.64, and 3.35 Å, which were consistent with reported values for the (111) plane of CuO and the (101) and (110) planes of SnO 2 , respectively, indicating the formation of CuO/SnO 2 heterostructures . The presence of periclases CuO and SnO 2 was also confirmed by the selected area electron diffraction (SAED) pattern (Figure j), which showed diffraction rings corresponding to reflections of CuO and SnO 2 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The surface morphology of KCl-CuO/SnO 2 was investigated by high-resolution TEM (HRTEM). As shown in Figure i, the interplanar spacings ( d ) were 2.32, 2.64, and 3.35 Å, which were consistent with reported values for the (111) plane of CuO and the (101) and (110) planes of SnO 2 , respectively, indicating the formation of CuO/SnO 2 heterostructures . The presence of periclases CuO and SnO 2 was also confirmed by the selected area electron diffraction (SAED) pattern (Figure j), which showed diffraction rings corresponding to reflections of CuO and SnO 2 .…”
Section: Resultssupporting
confidence: 86%
“…As shown in Figure 2i, the interplanar spacings (d) were 2.32, 2.64, and 3.35 Å, which were consistent with reported values for the (111) plane of CuO and the (101) and (110) planes of SnO 2 , respectively, indicating the formation of CuO/SnO 2 heterostructures. 24 The presence of periclases CuO and SnO 2 was also confirmed by the selected area electron diffraction (SAED) pattern (Figure 2j), which showed diffraction rings corresponding to reflections of CuO and SnO 2 . The elemental compositions and distributions of the KCl-CuO/SnO 2 composites were evaluated by energy-dispersive X-ray spectroscopy (EDS) mapping.…”
Section: Fabrication Of Humidity Sensorsmentioning
confidence: 72%
“…The molecular hybridization technique has garnered a lot of attention over the last two decades as a promising strategy for drug discovery and developing novel pharmacophores with biological multifunctions. 3,4 The combination of two separate bioactive compounds with adjuvant properties 5 and differing modes of action might be an appropriate way to boost the potency and increase the selectivity of the hybrid molecule toward pathogens and cancer cells over normal ones and hence reduce their adverse effects. 6,7 However, despite the success of the hybrid method in antimalarial 8 and anticancer 9,10 drug development, there is still a lack of research in the field of antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest value of the energy bandgap exhibited maximum antimicrobial activities in that electrons are excited from the valance band to the conduction band with small energy. For example, Pandey et al [132] showed the relationship between the energy bandgap and the antimicrobial activity of ZnO, ZnO-Ag 2 O/Ag, ZnO-CuO, and ZnO-SnO 2 against P. aeruginosa, K. pneumoniae, A. baumannii, and C. albicans pathogens. The antimicrobial activity increases as the bandgap of the nanocomposite decreases.…”
Section: Factor Affecting the Antimicrobialmentioning
confidence: 99%
“…Effect of energy bandgap on the antimicrobial activity of ZnO, ZnO-Ag 2 O/Ag, ZnO-CuO, and ZnO-SnO 2 against different pathogens[132].…”
mentioning
confidence: 99%